The Brian D. Jones Site (4-10B): A Multi-Component Paleoindian Site in Southern New England. (2nd April 2020) - Leslie, David E.; Sportman, Sarah P.; Jones, Brian D.
ABSTRACT: The Brian D. Jones Site (4-10B), in Avon, Connecticut, provides important information about subsistence, settlement patterns, and tool technology in the Early Paleoindian period in the American Northeast. Flaked lithic technology dominates the artifact assemblage, but large numbers of formal flaked tools and expedient tool forms, as well as charred botanicals and calcined bone fragments, were also recovered. Research is ongoing and is focused on understanding site-formation processes, raw-material procurement, tool production, and paleoenvironmental reconstruction to situate the site within its regional context.